Identification and functional characterization of zebrafish K2P10.1 (TREK2) two-pore-domain K+ channels - Gierten, Jakob; Hassel, David; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Biochimica et biophysica acta. General subjects, 2012)
Two-pore-domain potassium (K2P) channels mediate K+ background currents that stabilize the resting membrane potential and contribute to repolarization of action potentials in excitable cells. The functional significance of K2P currents in cardiac electrophysiology remains poorly understood. Danio rerio (zebrafish) may be utilized to elucidate the role of cardiac K2P channels in vivo. The aim of this work was to identify and functionally characterize a zebrafish otholog of the human K2P10.1 channel. K2P10.1 orthologs in the D. rerio genome were identified by database analysis, and the full zK2P10.1 coding sequence was amplified from zebrafish cDNA. Human and zebrafish K2P10.1 proteins share 61% identity. High degrees of conservation were observed in protein domains relevant for structural integrity and regulation. K2P10.1 channels were heterologously expressed in Xenopus oocytes, and currents were recorded using two-electrode voltage clamp electrophysiology. Human and zebrafish channels mediated K+ selective background currents leading to membrane hyperpolarization. Arachidonic acid, an activator of hK2P10.1, induced robust activation of zK2P10.1. Activity of both channels was reduced by protein kinase C. Similar to its human counterpart, zK2P10.1 was inhibited by the antiarrhythmic drug amiodarone. In summary, zebrafish harbor K2P10.1 two-pore-domain K+ channels that exhibit structural and functional properties largely similar to human K2P10.1. We conclude that the zebrafish represents a valid model to study K2P10.1 function in vivo.